Enhancing thermochemical energy storage density of magnesium‐manganese oxides. Issue 5 (26th August 2019) - King, Keith; Randhir, Kelvin; Petrasch, Joerg; Klausner, James
Abstract: Three approaches for enhancing the energy density of magnesium‐manganese oxide porous reactive materials for thermochemical energy storage (TCES) are investigated: adjusting the mole ratio, lowering the oxygen partial pressure during thermal reduction, and transition metal oxide doping. The manganese‐to‐magnesium molar ratios are varied to determine the composition yielding maximal energy density. The increase in energy density by lowering the oxygen partial pressure during the reduction step is also studied. Volumetric oxygen exchange capacities are measured for every case considered. Finally, the effects of doping magnesium‐manganese oxide with cobalt oxide, iron oxide, zinc oxide, and nickel oxide on the TCES properties are examined. We found the optimal Mn/Mg ratio for maximum volumetric energy density is in the vicinity of 1/1, achieving 1813 ± 175, 2178 ± 204, and 2323 ± 281 MJ m −3 for oxygen partial pressures of 0.2, 0.05, and 0.01 atm during thermal reduction, respectively; lowering the oxygen partial pressure below atmospheric during thermal reduction enhances oxygen exchange capacities and improves the energy density between 10%‐42% and 24%‐55% for oxygen partial pressures of 0.05 and 0.01 atm, respectively, with the greatest increases observed for high manganese content samples; and, doped samples exhibit reduced oxygen exchange and questionable reactive stability, thus appearing to reduce energy density.